Managing Unilateral Market Power in Electricity - Wolak, Frank A. (World Bank, Washington, DC, 2012)
This paper first describes those features of the electricity supply industry that make a prospective market monitoring process essential to a well-functioning wholesale market. Some of these features are shared with the securities industry, although the technology of electricity production and delivery make a reliable transmission network a necessary condition for an efficient wholesale market. These features of the electricity supply industry also make antitrust or competition law alone an inadequate foundation for an electricity market monitoring process. This paper provides examples of both the successes and failures of market monitoring from several international markets. More than 10 years of experience with the electricity industry restructuring process has shown that market failures are more likely and substantially more harmful to consumers than other market failures because of how electricity is produced and delivered and the crucial role it plays in the modern economy. Wholesale market meltdowns of varying magnitudes and durations have occurred in electricity markets around the world, and many of them could have been prevented if a prospective market monitoring process backed by the prevailing regulatory authority had been in place at the start of the market.